Changing groundwater discharge dynamics in permafrost regions. (3rd August 2018) - Lamontagne-Hallé, Pierrick; McKenzie, Jeffrey M; Kurylyk, Barret L; Zipper, Samuel C
Abstract: Permafrost thaw due to climate warming modifies hydrological processes by increasing hydrological connectivity between aquifers and surface water bodies and increasing groundwater storage. While previous studies have documented arctic river baseflow increases and changing wetland and lake distributions, the hydrogeological processes leading to these changes remain poorly understood. This study uses a coupled heat and groundwater flow numerical model with dynamic freezing and thawing processes and an improved set of boundary conditions to simulate the impacts of climate warming on permafrost distribution and groundwater discharge to surface water bodies. We show a spatial shift in groundwater discharge from upslope to downslope and a temporal shift with increasing groundwater discharge during the winter season due to the formation of a lateral supra-permafrost talik underlying the active layer. These insights into changing patterns of groundwater discharge help explain observed changes in arctic baseflow and wetland patterns and are important for northern water resources and ecosystem management.